Islam and Democracy: In Search of a Viable Synthesis - Effendy, Bahtiar (Studia Islamika, 1995)
Democracy is actually a concept that is understood and practiced heterogeneous. However, there are basic elements or "family resemblence" of democracy: the process of elite recruitment and freely through open competition, and the existence of the right to vote on the basis of universal suffrage. Are these two elements can not be accepted and practiced in Islamic countries? The problem is very dependent on how Islam is understood. During this time of political observers tend to define Islam as a monolithic religion. Huntington and Fukuyama, for example, the view that Islam is essentially incompatible with democracy. Islam is seen that seed saving practices threaten liberal.DOI:Â 10.15408/sdi.v2i4.818